Tinjauan Sistematis Kepemimpinan Transformasional Terhadap Kinerja Karyawan - Risma Ardiati; Rizki Akbar; Reza Amalia; Rafi Fito; Muadzin Nur Mubarok (Indo Publishing, 2026)
Transformational leadership is one of the leadership styles considered effective in improving employee performance, especially in organizations facing the demands of change and workplace dynamics. This article aims to systematically analyze the influence of transformational leadership on employee performance based on previous research results. The method used is a Systematic Literature Review (SLR) by reviewing relevant national and international scientific articles on transformational leadership and employee performance. The findings indicate that transformational leadership has a positive and significant impact on employee performance, reflected in increased work motivation, organizational commitment, as well as work quality and productivity. Thus, the implementation of transformational leadership can be an important strategy for organizations in efforts to sustainably improve employee performance.